4 - Hegemony, Ideology and Political Journalism in Democratic Malawi’s Broadcasting Media - Linje Manyozo, (Africa Media Review, 2004)
For the first three decades following independence from Britain in 1964, the governance of Malawi was a political dictatorship under President Dr. Hastings Kamuzu Banda and his Malawi Congress Party (MCP). The country adopted a multiparty constitution in 1993 through a national referendum. Bakili Muluzi and his United Democratic Front (UDF) emerged winners of the 1994 general elections and formed a government. The UDF also won the 1999 and 2004 elections. In a multiparty democracy, the right to freedom of expression should ideally empower journalists to provide in-depth and balanced reporting on issues that affect the disadvantaged populace, the majority of which lives in abject poverty. The media’s attempts at providing accurate and balanced information have, however, intensified tensions with the ruling politburo. Building on the case of four journalists who were dismissed from the country’s public broadcaster, the Malawi Broadcasting Corporation (MBC) Radio, this paper draws from Gramscian concepts of ideology and hegemony to critique the practice of political journalism in Malawi’s broadcasting media. It seeks to explore how oppressive political regimes stifle media freedom and how all this leads to the emergence of popular culture as a form of alternative media.